Pretreatment fatigue in breast cancer patients: comparison with healthy controls and associations with biopsychosocial variables - Blickle, Patricia; Schmidt, Martina; Steindorf, Karen (Cancer medicine, 2025)
Objective Cancer-related fatigue is one of the most common burdens of cancer patients. To date, most studies focused on fatigue during or after treatment. However, investigation of pretreatment fatigue is crucial to identify causal or risk factors other than cancer therapy and to enable timely fatigue management. Methods Two hundred and thirty-two breast cancer patients (mean age = 55.6) and 41 healthy participants (mean age = 49.3) were recruited via the National Center for Tumor Diseases (NCT) Heidelberg. Patient-reported outcomes were assessed with the EORTC QLQ-FA12 for fatigue, the EORTC QLQ-C30 for functioning, the STAI for anxiety, the CESD-R for depression and the PSQI for sleep disturbance. Descriptive analyses and logistic regression models were performed using baseline data before start of cancer treatment. The thresholds of clinical importance (TCI) were applied to test for clinically relevant fatigue. Results Compared to the healthy participants, patients scored significantly higher in physical, emotional, and total fatigue, in depression, in global health status and in all functioning scales except cognitive function (all p < 0.01). 48.7% of all patients reported clinically relevant fatigue. Being younger, being obese, having low education, or low social support was associated with a higher likelihood of clinically relevant fatigue before treatment. Higher depression and anxiety scores, poorer sleep quality and global health status, and impaired functioning seemed to get along with an increased likelihood of scoring above the TCI of fatigue (all p < 0.001). Conclusions Our study results suggest that fatigue screening, patient-centered fatigue education and psychosocial support may be needed already from the time of cancer diagnosis.
Gesehen am 30.09.2025